Prospects of winter rye breeding for bread baking - E. N. Shabolkina; A. A. Bisharev; N. V. Anisimkina; M. V. Belyaeva (Зерновое хозяйство России, 2019)
The rye production decrease in the Russian Federation is associated with low competitiveness, as well as the insufficient breeding improvement of newly developed varieties with a number of traits. Winter rye for food occupies a large segment of the modern market, so it is necessary to grow varieties that are suitable not only for the production of alcohol, starch and fodder, but also for baking purposes with high biochemical and technological properties. The purpose of our research is to find out the breeding prospects for winter rye varieties with improved baking advantages in the Middle Volga region. The study was conducted from 2015 to 2017 on the basis of the Samara RIA named after N. M. Tulaykov. The object of the research was some zoned and promising winter rye varieties. The influence of changing growing conditions on yield, productivity elements and grain quality has been evaluated. It has been established that over the years of study the winter rye variety “Bezenchukskaya 110” was more stable and adaptable to the growing conditions (regression coefficient of 0.88) than the standard variety and its productivity reliably exceeded the yield of the standard variety (50.3 hwt/ha) by 2.1 hwt/ha. In 2015 and in 2016 the varieties “Bezenchkuyskaya 87” and “Roksana” showed the best baking properties, namely 515–575 cm3 of maximum bread volume. In 2016 the variety “Bezenchukskaya 110” showed the best biochemical parameters (282 p. falling number; 780 e. a. height of amylogram) and baking quality (4.2 points of general baking assessment). In the conditions of the Middle Volga region, it is necessary to carry out breeding of winter rye varieties for food, namely with improved technological and baking advantages.